An MTF1 binding site disrupted by a homozygous variant in the promoter of ATP7B likely causes Wilson Disease. (December 2018) - Chen, Heidi; Jagadeesh, Karthik; Birgmeier, Johannes; Wenger, Aaron; Guturu, Harendra; Schelley, Susan; Bernstein, Jonathan; Bejerano, Gill
Abstract Approximately 2% of the human genome accounts for protein-coding genes, yet most known Mendelian disease-causing variants lie in exons or splice sites. Individuals who symptomatically present with monogenic disorders but do not possess function-altering variants in the protein-coding regions of causative genes may harbor variants in the surrounding gene regulatory domains. We present such a case: a male of Afghani descent was clinically diagnosed with Wilson Disease—a disorder of systemic copper buildup—but was found to have no function-altering coding variants inATP7B (ENST00000242839.4), the typically causative gene. Our analysis revealed the homozygous variant chr13:g.52, 586, 149T>C (NC_000013.10, hg19) 676 bp into theATP7B promoter, which disrupts a metal regulatory transcription factor 1 (MTF1) binding site and diminishes expression of ATP7B in response to copper intake, likely resulting in Wilson Disease. Our approach to identify the causative variant can be generalized to systematically discover function-altering non-coding variants underlying disease and motivates evaluation of gene regulatory variants.